Measuring and evaluating technical efficiency of a Libyan construction companies through data envelopment analysis / Abdullah Ahmad A. Eltaief , Saadiah Mohamad and Badrul Hisham Kamaruddin - Ahmad A. Eltaief, Abdullah; Mohamad, Saadiah; Kamaruddin, Badrul Hisham (Institute of Business Excellence and UPENA, 2010)
This paper attempts to investigate this claim through measuring the technical efficiency for 26 companies surveyed in 1995-2005 in Libyan construction industry. In measuring technical efficiency data envelopment analysis (DEA) will be adopted. Further, this paper looks at determine the level of technical efficiency where as the input variables comprise assets, equity and number of employees. The output variables used were revenue and profit. The results from this study show that the majority of the Libya companies are operating inefficiency. The overall (pooled) technical efficiency (TE) estimate was 0.807. Whereas 69 percent of the firms were operate above the average, and 31 percent below it. Only 2 firms scored full efficiency (TE = 1.00) while 24 others were inefficient. Detailed analysis showed that majority of firms suffer over employment of workers, overstatement of assets and equity and using obsolete technology. The results also showed that larger firms are more efficient than the smaller firms, and technical efficiency is not a consequence of firm's age, and that change of government policy has a strong effect on technical efficiency. That is, after the government implemented the open door policy, technical efficiency scores gradually increase.